2012
DOI: 10.1111/j.1749-6632.2012.06623.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid–catecholamine interplay within the composite thymopoietic regulatory network

Abstract: This paper highlights the multiple putative thymic and extrathymic points of intersection and interaction between glucocorticoids (GCs) and catecholamines (CAs)—the end‐point mediators of the major routes of communication between the brain and the immune system—in the context of intricate thymic T cell–developmental tuning. More specifically, we discuss in detail findings indicating that adrenal GCs can influence thymopoiesis by adjusting directly and/or indirectly (through modulation of pituitary and local AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 92 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…One way that GCs can influence BP is by influencing CA biosynthesis and secretion. GCs directly increase the release of CAs by sympathetic nerves and adrenal medullary cells ( 127 , 128 ). Early evidence of GC control over adrenal CA biosynthesis was demonstrated in experiments performed by Wurtman and Axelrod ( 129 ), who reported that ablation of the pituitary gland decreases PNMT activity, which can be restored by addition of ACTH or GC ( 129 ).…”
Section: Introductionmentioning
confidence: 99%
“…One way that GCs can influence BP is by influencing CA biosynthesis and secretion. GCs directly increase the release of CAs by sympathetic nerves and adrenal medullary cells ( 127 , 128 ). Early evidence of GC control over adrenal CA biosynthesis was demonstrated in experiments performed by Wurtman and Axelrod ( 129 ), who reported that ablation of the pituitary gland decreases PNMT activity, which can be restored by addition of ACTH or GC ( 129 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although research has uncovered that ARs and GRs influence inflammatory responses in the body and regulate physiological homeostatic processes, few studies have elucidated whether these receptors interact during the activation of molecular signaling pathways at the level of second messengers [126][127][128]. Given the diversity and the interconnectivity of AR/GPCR-mediated signaling, spanning various second messengers, and GR-mediated transcriptional activity, along with cooperativity with other transcription factors influencing the expression of about 10-20% of the human genome (as reviewed in [25]), it is conceivable that there are interactive influences on the physiological effects of AR and GR activation.…”
Section: Potential Interactive Roles Of Ars and Grs In Inflammatory Mechanismsmentioning
confidence: 99%
“…The interactive influence of glucocorticoids and catecholamines has also been reported at the level of the neuroendocrine system. Glucocorticoid modulation of pituitary adrenocorticotropic hormone (ACTH) release can alter thymus catecholamine availability through its influence on sympathetic nerve terminals, and change AR gene expression [128]. It has been suggested that dexamethasone-induced GR activation interferes with the trafficking and degradation of the β-arrestin-α 2 cAR complex in human neuroblastoma cells [129].…”
Section: Potential Interactive Roles Of Ars and Grs In Inflammatory Mechanismsmentioning
confidence: 99%
“…In addition to being a principal regulator of the HPA axis, CRH also causes stimulation of SNS activity [77]. Glucocorticoids stimulate biosynthesis, secretion and release of catecholamines (CA) by sympathetic nerves and adrenal medullary cells [78], and enhance vasoconstrictor effects of angiotensin-II and catecholamines and it has also been implicated in endothelial dysfunction [79]. Thus, synergistic and prolonged actions of CRH, glucocorticoids and catecholamines cause central and autonomic dysregulation of cardiovascular system, which eventually leads to hypertension.…”
Section: Over Activity Of Hpa Axismentioning
confidence: 99%